Rapid Eye Movement Sleep Behavior Disorder: Abnormal Cardiac Image and Progressive Abnormal Metabolic Brain Pattern. Issue 3 (19th November 2021) - Janzen, Annette; Kogan, Rosalie V.; Meles, Sanne K.; Sittig, Elisabeth; Renken, Remco J.; Geibl, Fanni F.; Booij, Jan; Stormezand, Gilles; Luster, Markus; Mayer, Geert; Leenders, Klaus L.; Oertel, Wolfgang H.
ABSTRACT: Background: Isolated rapid eye movement sleep behavior disorder (iRBD) is prodromal for α‐synucleinopathies. Objective: The aim of this study was to determine whether pathological cardiac [ 123 I]meta‐iodobenzylguanidine scintigraphy ([ 123 I]MIBG) is associated with progression of [ 18 F]fluorodeoxyglucose‐positron emission tomography–based Parkinson's disease (PD)‐related brain pattern (PDRP) expression in iRBD. Methods: Seventeen subjects with iRBD underwent [ 18 F]fluorodeoxyglucose‐positron emission tomography brain imaging twice ~3.6 years apart. In addition, [ 123 I]MIBG and [ 123 I] N ‐ω‐fluoropropyl‐2β‐carbomethoxy‐3β‐(4‐iodophenyl)nortropane single‐photon emission computed tomography ([ 123 I]FP‐CIT‐SPECT) at baseline were performed. Olfactory, cognitive, and motor functions were tested annually. Results: Twelve of 17 subjects had pathological [ 123 I]MIBG. At baseline, 6 of 12 of these expressed the PDRP (suprathreshold PDRP z score). At follow‐up, 12 of 17 subjects had suprathreshold PDRP z scores, associated with pathological [ 123 I]MIBG in 92% and with pathological [ 123 I]FP‐CIT‐SPECT in 75%. Subjects with pathological [ 123 I]MIBG had higher PDRP z score change per year ( P =  0.027). Three subjects phenoconverted to PD; all had pathological [ 123 I]MIBG and [ 123 I]FP‐CIT‐SPECT, suprathreshold baseline PDRP z scores, and hyposmia. Conclusions: Pathological [ 123 I]MIBG was associated with progressive and suprathreshold PDRP z scores at follow‐up. Abnormal [ 123 I]MIBG likely identifies iRBD as prodromal PD earlier than pathological [ 123 I]FP‐CIT‐SPECT. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society